Arctic LNG cluster: new opportunities or new treats?. Issue 1 (July 2020) - Razmanova, Svetlana; Steblyanskaya, Alina
Abstract: Construction and further operation of the "Nord stream", "Nord stream 2" and "Power of Siberia" gas pipelines are a crucial element in the development of cooperation between Russia, the EU and China in the gas sector. Nevertheless, the Russian Federation considers not only gas exports via pipelines but also the supply of liquefied natural gas (further-LNG) as a priority area in the regional markets. Nowadays, the LNG market is a derivative of the traditional gas market and has certain competitive advantages over pipeline gas supplies. Many countries, including the Russian Federation, are trying to consolidate their positions in the relatively new and growing LNG market. In the Paper, the Authors consider the main Russian LNG project's strength and weaknesses. At the same time, there are several of specific problems that need to be taken into account in the development of Arctic hydrocarbon reserves. The creation of an LNG cluster with an annual capacity of up to 140 million tons on the territory of the Yamal-Nenets Autonomous district is associated with significant risks. Among the most crucial risks are: competition for the LNG market share in the EU and Asia-Pacific countries started between the US and Russia, as well as Australian, Indonesian and Middle Eastern companies; significant volatility in energy prices on the World markets, and in particular in the EU and Asia-Pacific markets; high cost of Russian LNG projects and their limited funding under sanctions restrictions.